A perspective on Freud's theories in relation to self-harming behaviour - Guan, Teik Ee; Poh, Li Lau (Penerbit UMS, 2019)
Self-harming is intentional self-destructive behaviour, although it is not necessarily suicidal. It is common not only in the West, but also in oriental countries like Malaysia. Many people question why adolescents harm themselves intentionally nowadays? What actually motivates them to do so? This conceptual paper explains the reasons behind such actions based on Freud’s theories. According to Freud, the constructs of id, ego and superego interact to form a person’s character. The id is our instinctual drive that ignores consequences when it acts, while the ego is our common sense faculty, responsible for working out proper plans that are acceptable to society. The superego is moralistic; its role is to prevent the id from prevailing when it thinks that it is wrong. In daily life, individuals strive to achieve homoeostasis whenever pain occurs through the distribution of these energies. As adolescence is a stage of overwhelming experience, in order to release the tension that arises, the id leads us into instinctual desire and problematic behaviour, such as self-harming. It is only through rigorous training that the ego can function well and overcome the driving force of the id to avoid any problematic behaviour. When the superego leads, adolescents will be seen as rigid and cannot tolerate any flaws in their life. In order to have a balanced and healthy personality, adolescents need to have a good blend of these three constructs. Thus, understanding what lies behind an action can enable us to have a deeper understanding of why adolescents engage in self-harming behaviour.